(untitled) (International Journal of Built Environment and Sustainability, 2023)
Salah Al-Din Governorate, including the study area located in Baiji district, is considered an important agricultural area in Iraq. As these areas have become mainly dependent on ground water. As this led to the depletion of underground water reservoirs, which turned many of the wells into unproductive or poorly productive wells. Therefore, there was a need to re-evaluate the hydraulic properties in the region, and then nominate sites for drilling new wells with high productivity according to the data of this evaluation. Selecting new well sites is becoming an increasingly difficult task. All hydraulic properties and geological factors must be taken into consideration. On the other hand, GIS technology is considered one of the most reliable techniques used in the process of determining the most appropriate sites. All this is done according to the use of algorithms that depend mainly on the importance of each factor and dealing with it as a class within the selection and nomination mechanism. In this study, fuzzy logic was applied through geographic information systems technology to determine the optimum sites for new well drilling with high productivity, based on the analysis of hydro-electrical parameters of the aquifer in the region. The research region was divided into four groups by the findings map: excluded, low suitability, moderate suitability, and high suitability. The area for each suitability category was 172.53, 269.76, 131.89, 127.26 km2 respectively.